Time Efficiency on Computational Performance of PCA, FA and TSVD on Ransomware Detection - Benni Purnama; Deris Stiawan; Darmawijoyo Hanapi; Mohd. Yazid Idris; Sharipuddin Sharipuddin; Nurul Afifah; Rahmat Budiarto (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2022)
Ransomware is able to attack and take over access of the targeted user'scomputer. Then the hackers demand a ransom to restore the user's accessrights. Ransomware detection process especially in big data has problems interm of computational processing time or detection speed. Thus, it requires adimensionality reduction method for computational process efficiency. Thisresearch work investigates the efficiency of three dimensionality reductionmethods, i.e.: Principal Component Analysis (PCA), Factor Analysis (FA) andTruncated Singular Value Decomposition (TSVD). Experimental results onCICAndMal2017 dataset show that PCA is the fastest and most significantmethod in the computational process with average detection time of 34.33s.Furthermore, result of accuracy, precision and recall also show that the PCAis superior compared to FA and TSVD.